Integration of Remote Sensing and GIS for Mapping of Land Cover Change due to Flash Floods in Simangulampe, North Sumatra, Indonesia - Prihantarto, Wikan Jaya; Purnamasari, Eva; Ismail, Muhammad; Putri, Sri Kandi; Putri, Erisa Waspadi; Yudinugroho, Maulana (Iraqi Journal of Science, 2025)
Flash floods hit Simangulampe Village, North Sumatra, Indonesia, on December 1st, 2023. This incident resulted in loss of life, material damage, and environmental change around impacted areas. This study aims to map land cover changes due to flash floods and analyze the flash flood source area using remote sensing data integrated with GIS. Mapping was conducted using two Planet Scope images recorded before and after the disaster. The multispectral classification was used to obtain land cover maps from these images, and both of them were analyzed using the overlay method. 30 m SRTM DEM was used to delineate the watershed. Disaster source analysis assessed the extent of land cover change in the watershed upstream zone. The results showed a significant land cover change in the downstream zone due to debris material covering an area of 9.86 ha. The affected land cover was a built-up area of moderate and low-density vegetation. A source zone was found, characterized by an extent increase of bare soil upstream of 5.48 ha.